2005
DOI: 10.1002/bjs.5210
|View full text |Cite
|
Sign up to set email alerts
|

Operability and early outcome in 100 consecutive laparotomies for peritoneal malignancy

Abstract: Cytoreduction combined with intraperitoneal chemotherapy is an emerging technique with promising results in selected patients with peritoneal malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 27 publications
3
25
1
1
Order By: Relevance
“…In other published series recurrence or progression rates of 40-70% have been reported. 6,7,15 As in other series, we observed that pathological subtype and result of initial cytoreduction were the dominant factors related to progression. 3,10,17 The diagnosis of progressive disease is not always easy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In other published series recurrence or progression rates of 40-70% have been reported. 6,7,15 As in other series, we observed that pathological subtype and result of initial cytoreduction were the dominant factors related to progression. 3,10,17 The diagnosis of progressive disease is not always easy.…”
Section: Discussionsupporting
confidence: 79%
“…A number of series using this approach has now been published, showing indeed that longterm disease free and progression free survival can be improved. [3][4][5][6]15,16 Still, even after this combined modality treatment progression was observed in our series in 41% of cases. In other published series recurrence or progression rates of 40-70% have been reported.…”
Section: Discussionsupporting
confidence: 41%
“…We have reported our experience with similar results and projected 5 and 10 year disease free survival rates of 70 -80% in favourable cases of PMP [7].…”
Section: Introductionsupporting
confidence: 60%
“…The techniques have been previously described [7]. In total 29 patients received intra-operative, intraperitoneal, Mitomycin C (10mg/m2) for 1 hour at 42C.…”
Section: Surgery and Hipecmentioning
confidence: 99%
“…Peritonectomy and multivisceral resections were performed depending on the distribution pattern of peritoneal neoplasia and included hemi-/pancolectomy, omentectomy (omentum majus/minus), splenectomy, cholecystectomy, resection of the visceral surface of the liver, gastrectomy, rectal resection, partial or total peritonectomy, hysterectomy and/or adnectomy, as described previously [24] (table 2). HIPEC was scheduled for the 5th postoperative day by using the closed technique.…”
Section: Methodsmentioning
confidence: 99%